Para Lunan a collection of third places to integrate the fragmented city of Calamba - Encinas, Philippe Joseph D.; Sicam, Olivia Alma (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
This study is an investigation about the effects of Metro Manila's urban sprawl to its periphery, specifically to Calamba City, the center of CALABARZON region and an exploration on the architectural solutions that can address the issue. From the historical narratives, population growth statistics, and urban land cover change of Calamba City, this study determined that the local is experiencing urban fragmentation as a result of the rapid horizontal expansion of the capital region. There are two elements at play in fragmentation of the city; the fragments and the boundaries or edges, which when present in high density causes deeper sub-problems, namely social exclusion, traffic congestion, and lack of architectural contextualization. In order to address these problems, the 3-Cs agenda: Citizen centered, Connected, and Coherent, was proposed.
In the design implementation, the project will be called Para-Lunan, a common ground for Calambenos of all socio-economic classes and backgrounds, who were forced to be alienated from each other brought by urban fragmentation. This architectural common ground is a collection of Third Places, the "living room" of the city, and the anti-thesis of borders and boundaries. Para-Lunan was designed to follow the incrementalism approach, like opening of the sites, breaking physical boundaries, and forging new connections; the second phase focused on creating a coherent and citizen centered design through building form and program that high contextualized on the users and the environment of the site; and lastly, the third phase doubled down on citizen centeredness of the design by providing a sustainable water supply system and allowing user customization and expansion of their spaces.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Fragmented city -- Calamba; Third places; Urban fragmentation -- Calamba